A comparison of income, expenditures, and home market value distributions using Luxembourg Income Study data from the 1990s - Eva Sierminska; Thesia I. Garner (Luxembourg Income Study (LIS), 2002)
The purpose of this paper is to review recent data made available through the Luxembourg Income Study (LIS) that include expenditures and asset valuations. The LIS data are augmented with comparable data from the U.S. Consumer Expenditure Survey. The surveys with expenditure data are reviewed in terms of collection units and variable definitions. Inequality statistics are produced and compared using income, expenditures, and market value of owned home. Rankings of countries by income and expenditure inequality are similar but not the same across the countries studied. Suggestions are made for the LIS to improve the expenditure data available following the COICOPS framework.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Disparitätsmaß; Haushaltsbudget-Statistik; USA